Designing a new sliding mode control for stochastic system with packet losses. Issue 9 (1st September 2020) - Ashrafi Bafghi, Mahdi; Delavarkhalafi, Ali
ABSTRACT: This paper is concerned with the design of sliding mode control (SMC) for a class of stochastic systems with packet losses. The information may encounter a kind of dropout during the transmission from the sensor to the controller. The probability distribution of packet dropout obeys Bernoulli process. A sliding function is constructed and it is shown that the state trajectories of the resultant SMC system can be driven onto the specified sliding surface in finite time. To prove the stability of the proposed method we use Lyapunov stability theorem. Finally, two numerical examples are provided to demonstrate the efficiency of the presented method.